Pictorial and spatial metaphor in the drawings of a culturally diverse group of women with fertility problems. (May 2020) - Refaie, Elisabeth EL; Payson, Alida; Bliesemann de Guevara, Berit; Gameiro, Sofia
Metaphor has been shown to be pervasive in the way people talk and write about a whole range of diseases, including infertility. Indeed, some of the most conventional of these metaphorical expressions have become so entrenched in particular discourse communities that they are used unconsciously and automatically, even by people who do not, in fact, agree with their underlying ideological implications. As the authors argue in this article, eliciting visual metaphors in the form of drawings may reveal the meaning-making processes of individuals in a way that more richly reflects their unique experiences, including those that challenge or disrupt dominant cultural models. Based on an analysis of drawings created by a group of women in Wales from diverse ethnic and religious backgrounds, the authors show the importance of taking into account both explicit pictorial metaphors and any metaphorical meanings suggested by spatial composition, as well as the specific socio-cultural context in which they were created.